What is Hospitality? - Kunwar, Ramesh Raj (The Gaze: Journal of Tourism and Hospitality, 2017)
This work has been fully based on review of several secondary sources, conceptual and applied discourses on hospitality education, management and research. The objective of studying this subject is to disseminate the knowledge of hospitality in the academia. Many scholars of hospitality across the world have produced different theoretical models, conceptual insights, pragmatic approaches and experiential perspectives which have become an impetus for understanding the hospitality as human phenomena, hospitality and hospitableness, the hospitality industry, its management, research, training and development as well as education in this specialized field of service and experience economy. As a purely academic discourse, the paper as a whole has been prepared by studying the origin, history, conceptualization, dimensions, interactions, typologies and neologism in hospitality. However, the present scholar could explore varying opinions on nature and functional coverage of hospitality and tourism, this study could identify many symbiotic relationships from different perspectives. It is believed that this study will serve instrumental for the learners, educators, researchers and professionals of hospitality and tourism. The GAZE Journal of Tourism and Hospitality, Vol. 8, 2017, Page: 55-115